The Effectiveness of Couples Therapy Based on the Gottman Method Among Iranian Couples With Conflicts: A Quasi-Experimental Study. Issue 3 (3rd July 2019) - Rajaei, Afarin; Daneshpour, Manijeh; Robertson, Janet
Abstract: This study examined the effectiveness of couple therapy based on the Gottman method in decreasing emotional divorce and improving verbal-nonverbal communication skills among Iranian couples dealing with conflicts. The design of the study was quasi-experimental with pretest and posttest, and a wait list control group. The sample for the study consisted of 14 voluntary couples who sought therapy at a mental health clinic in Iran. Participants were assessed using the Emotional Divorce Scale and Primary Communication Inventory questionnaires. Analysis of covariance models were used. Results of the study showed that the Gottman method reduced emotional divorce and improved their verbal-nonverbal communication skills ( P < .05).